2004
DOI: 10.1097/01.inf.0000106981.89572.d1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and sharing of Haemophilus influenzae strains colonizing healthy children attending day-care centers

Abstract: The degree of sharing of H. influenzae among children in this study suggests transmission of these potentially pathogenic microorganisms in day-care centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 32 publications
2
74
0
Order By: Relevance
“…Colonization of potential respiratory pathogens in the URT is very common in healthy children (Farjo et al, 2004). Our longitudinal carriage study indicated that the carriage of Strep.…”
Section: Association Between Colonization Of the Four Bacteriamentioning
confidence: 97%
See 1 more Smart Citation
“…Colonization of potential respiratory pathogens in the URT is very common in healthy children (Farjo et al, 2004). Our longitudinal carriage study indicated that the carriage of Strep.…”
Section: Association Between Colonization Of the Four Bacteriamentioning
confidence: 97%
“…Most carriage studies have focused on individually evaluating colonization by a single bacterium (O'Brien et al, 2003;Farjo et al, 2004;Greenberg et al, 2004). Recently, some carriage studies have reported the cooccurrence of a number of bacteria and suggested direct interactions such as interference or competition between the various bacterial species in the URT (Jacoby et al, 2007;Pettigrew et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Often disregarded as an oral contaminant, NTHi commonly colonizes the upper respiratory tract (36,37). However, this common human upper respiratory tract commensal is also a significant pathogen in the lower respiratory tract of patients with CF (11-13, 15, 38-40).…”
Section: Nthi In Early Cf Lung Diseasementioning
confidence: 99%
“…Historically, H. influenzae strains lacking a capsule were detected by their failure to react with antibodies directed against the six immunologically distinct capsular polysaccharides and were designated nontypeable, i.e., serotype negative, H. influenzae (NTHI) (33). Nontypeable strains predominate among commensal organisms (9,29) and those causing respiratory infections such as acute otitis media, sinusitis, or bronchitis, while serotypeable strains are isolated more often from clinical samples of patients with invasive infections such as bacteremia, meningitis, facial cellulitis, and septic arthritis. In addition, multilocus sequence typing has shown that NTHI strains are genetically widely variable, while serotypeable strains are more clonal (25).…”
mentioning
confidence: 99%